Undergraduate Latino Men Speak "Out" - Joshua C. Collins (Adult Education Research Conference, 2012)
Rosario, Schrimshaw, and Hunter‘s (2004) study of 145 lesbian, gay, and bisexual youth (ages 14-21) revealed, ―Latino youths reported similar levels of comfort with others knowing about their homosexuality as did White youths. However, like the Black youths, Latino youths had disclosed to fewer individuals than had White youths‖ (p. 226). In Latino communities, respect for authority often keeps young LGB-identified people from coming out of the closet about their sexuality to parents or other respected individuals (Rosario et al., 2004). However, these individuals also rely heavily on family and place a high value on those relationships, knowing ―they will not be abandoned‖ for being gay should they come out of the closet (p. 226).